(untitled) (Progressive Agriculture, 2013)
The present study was undertaken to find out the efficacy of vitamin E and/or vitamin C against mercury (Hg) induced toxicity in mice. Sixty mice were randomly divided into 5 equal groups (n=12). One group of mice (Group A) was kept as control and each of rest four groups (B, C, D and E) were fed with mercuric chloride (HgCl2) in drinking water @ 65 mg/L. In addition to HgCl2 alpha-tocopherol (vitamin E) @ 100 mg/L, ascorbic acid (vitamin C) @ 250 mg/L and combination of vitamin E and vitamin C at same dose were given to the mice of groups C, D and E respectively. All treatments were continued for 28 consecutive days. Four mice of each group were sacrificed on day 1, 14 and 28 and efficacy of vitamin E and vitamin C against Hg induced toxicity were evaluated by observing toxic signs, body weight, hemato-biochemical parameters and postmortem lesions. Mild (++) toxic signs as evident by reduced feed and water intake, salivation, vomiting, excitement, muscle tremor, ataxia, restlessness, incordination and ruffled hair coat were observed from 2nd week (group B) and from 3rd week (group C and D) by intoxication with HgCl2. Significant (P<0.01) reduction of body weight (18.38%) and hematological parameters i.e. TEC (19.88%), TLC (27.89%), Hb content (34.09%) and PCV (9.15%) were observed at day 28 in HgCl2 induced intoxicated mice (group B). At identical period in same group biochemical parameters i.e. AST (46.99%) and ALT (58.72%) increased significantly (p<0.01). Pinpoint hemorrhages throughout the liver and highly (++++) congested kidney was also observed at post mortem (group B). All the parameters i.e. toxic signs, body weight, hemato-biochemical and post mortem lesions were found to be slight (+) or mild (++) and/or improved in rest three groups of mice following treatment with vitamin E, vitamin C and combination of vitamin E and vitamin C. The present study reveals that vitamin E and C have a protective role against Hg poisoning. However, combination of vitamin E and C gave better results. DOI: http://dx.doi.org/10.3329/pa.v19i2.16949 Progress. Agric. 19(2): 93 - 100, 2008